Theory of antiskyrmions in magnets - Wataru Koshibae (Nature Portfolio, 2016)
Skyrmions are swirling topological magnetic textures that behave as if they were particles. Here, the authors present numerical simulations that describe the creation and destruction of these spin vortices in both chiral and dipolar magnets, and show what happens when skyrmions and antiskyrmions collide.